2021
DOI: 10.1155/2021/7891475
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Wake Safety Interval for Paired Approach Based on CFD

Abstract: In order to relieve the stress caused by the surge of flight flow, Closely Spaced Parallel Runways (CSPRs) have been built in many hub airports, and a paired approach mode has been applied to CSPRs in some countries. This paper proposes a method for optimizing the wake separation between aircrafts which utilizes a paired approach, aiming at reducing longitudinal separation by using computational fluid dynamics technology. Firstly, the model of the wake vortex field of the paired lead aircraft is constructed. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In 2021, Xin et al. used CFD to simulate the aircraft wake flow field during the approach phase and established a safety interval for paired approach based on simulation results 17 . The technology of using CFD method to study aircraft wake has been relatively mature, but no scholar has applied CFD technology to the study of PD wake spacing yet.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Xin et al. used CFD to simulate the aircraft wake flow field during the approach phase and established a safety interval for paired approach based on simulation results 17 . The technology of using CFD method to study aircraft wake has been relatively mature, but no scholar has applied CFD technology to the study of PD wake spacing yet.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation results demonstrated that the evolution of vortices upstream and downstream of the aircraft was asymmetric, with the downstream vortices decaying at a faster rate, and the wake vortex dissipation velocity increasing with higher crosswind velocities. He et al [20] established an aircraft wake vortex model for paired approach procedures, and conducted CFD numerical simulations to analyze the wake characteristics. Based on the simulation results, they proposed an optimization method for longitudinal safety separation of paired aircraft wake vortices.…”
Section: Introductionmentioning
confidence: 99%